2008
DOI: 10.2174/138161208786898770
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorothioate-Stimulated Cellular Uptake of siRNA: A Cell Culture Model for Mechanistic Studies

Abstract: The phosphorothioate(PS)-stimulated cellular uptake of naked short interfering RNA (siRNA) into mammalian cells indicates a promising new mechanistic strategy because it makes use of a caveosomal, rather than an endosomal pathway, which is used by the majority of known delivery systems. This PS-stimulated mode delivers large amounts of siRNA primarily into the perinuclear space which is related to measurable though moderate target suppression. The observed limited efficacy seems to be related to intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Assuming a 1:1 molar stoichiometry in the antisense mechanism of action, one would theoretically expect antisense modalities to be efficacious in the femtomolar range. Our data, however, reinforce observations by others that collectively point to a rate-limiting step(s), including cellular uptake, intracellular transport, and differential cellular compartmentalization, of HCV and oligonucleotide therapeutics (3,8,10,25).…”
supporting
confidence: 90%
“…Assuming a 1:1 molar stoichiometry in the antisense mechanism of action, one would theoretically expect antisense modalities to be efficacious in the femtomolar range. Our data, however, reinforce observations by others that collectively point to a rate-limiting step(s), including cellular uptake, intracellular transport, and differential cellular compartmentalization, of HCV and oligonucleotide therapeutics (3,8,10,25).…”
supporting
confidence: 90%
“…Although Rh110-labelled siRNA phosphorothioate (PTO)-modified ON (TM6-6) entered into ECV304 cells [96], similar results could not be obtained with either the human T-lymphoma cell line Jurkat 17 [97] or the mouse B-lymphoid cell line BJA-B [98]. In the absence of PTOs, the uptake of the siRNA was reduced and the molecules distributed throughout the cytoplasm [99].…”
Section: Cytoplasmatic Entrymentioning
confidence: 99%
“…However, when entry of siRNA has been demonstrated, there is an apparent dose-dependent siRNA-mediated suppression of lamin A/C in primary human umbilical vein endothelial cells [96,99]. Perhaps more importantly, Skog et al [81] showed that mRNA and miRNA can be taken up by normal host cells including brain and microvascular endothelial cells.…”
Section: Cfrnamentioning
confidence: 99%
“…This discovery and strongly related phenomenon of synthetic short interfering RNA duplexes (siRNA) are thought to be promising tools for gene silencing. Interestingly, phosphorothioate oligonucleotides (in which one of the nonbridging phosphate O-atoms is replaced with a S-atom [20] (PS-Oligos; 2), were found to stimulate cellular uptake of naked siRNAs into mammalian cells, and this indicated a promising mechanistic strategy for a new delivery systems [21]. Recent progress in this dynamically developed area has been compiled in many reviews [22 -25].…”
mentioning
confidence: 99%
“…A first method for stereochemically controlled chemical synthesis of PS-Oligos, which was elaborated by Stec et al [91], is based on a quite different chemistry employing P-diastereoisomerically pure nucleoside monomers possessing at the 3'-O-position the 2-thioxo-1,3,2-oxathiaphospholane moiety (19; Scheme 3), alternatively substituted at C(4) with either two Me groups (20) [92] or pentamethylene ring in a spiro arrangement (21) [93]. These substituents enhance a differentiation in chromatographic mobility of diastereoisomers, rendering their separation less laborious.…”
mentioning
confidence: 99%